2012
DOI: 10.1111/j.1742-481x.2011.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

The economic benefits of negative pressure wound therapy in community‐based wound care in the NHS

Abstract: The human and economic costs of wounds are of major concern within today's National Health Service. Advances in wound care technology have been shown to be beneficial both in healing and in relation to patient quality of life. Negative pressure has often been associated with high-cost care and restricted to use in the secondary care setting. There is growing use of negative pressure within the community, and this has the potential to benefit the patient and the service by providing quality care in the patient'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 8 publications
1
44
0
2
Order By: Relevance
“…To have a reliable financed treatment pathway for these patients could potentially lead to huge cost savings for the healthcare system as inpatient care is in general more expensive than treatment in the outpatient sector. 24 Another obstacle for the reimbursement in this area is the fact that the usage and dressing changes for NPWT requires experience and special skills. Therefore in contrast to other wound care products the patient or a relative cannot do the dressing change on their own.…”
Section: Discussionmentioning
confidence: 99%
“…To have a reliable financed treatment pathway for these patients could potentially lead to huge cost savings for the healthcare system as inpatient care is in general more expensive than treatment in the outpatient sector. 24 Another obstacle for the reimbursement in this area is the fact that the usage and dressing changes for NPWT requires experience and special skills. Therefore in contrast to other wound care products the patient or a relative cannot do the dressing change on their own.…”
Section: Discussionmentioning
confidence: 99%
“…Since most venous ulcers are treated in the outpatient setting, this has resulted in limited use of NPWT on VLUs in general though significant evidence supports the benefit of NPWT for VLUSs healing. [14][15][16][17][18][19][20][21][22][23] Recently, a single use, mechanically powered (MP) NPWT system has been developed called the Smart Negative Pressure (SNaP Ò ) Wound Care System (Spiracur, Inc., Sunnyvale, CA). 24 Instead of using an electric pump to generate negative pressure, the MP device utilizes specialized springs to generate a preset continuous subatmospheric pressure level to the wound bed.…”
Section: Introductionmentioning
confidence: 99%
“…The documented benefits of negative pressure wound therapy are known to include reduction in the number of required dressing changes and in nursing time. 38 A previous randomized controlled trial of the SNaP negative pressure system versus the commonly used VAC (KCIÔ) system indicated that the mean application time for SNaP was significantly less ( p < 0.0001) than that of the VAC system for all follow-up visits combined. 29 The mean time taken for the application of the SNaP Wound Care System in this study was 7 min 11 s (range 01:00-50:00 min).…”
Section: Evaluation Of a Novel Tnp Device In Healing Chronic Woundsmentioning
confidence: 99%